2018
DOI: 10.5194/acp-2018-348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agricultural harvesting emissions of ice nucleating particles

Abstract: <p><strong>Abstract.</strong> Agricultural activities can modify natural ecosystems and change the nature of the aerosols emitted from those landscapes. The harvesting of crops can loft plant fragments and soil dust into the atmosphere that can travel long distances and interact with clouds far from their sources. In this way harvesting may contribute substantially to ice nucleating particle (INP) concentrations, especially in regions where agriculture makes up a large… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 0 publications
0
14
3
Order By: Relevance
“…Across the entire ACAPEX study, number concentrations of INPs ( n INP ) ranged from near 0 up to a few ~10s L −1 at temperatures from −20 to −30 °C (Figure ), which are typical for ambient n INP values at these temperatures in relatively clean environments (DeMott et al, ). While concentrations as high as 100–1,000 L have been observed in heavily dust impacted environments (Boose et al, ; DeMott et al, ) and 100s L −1 in agricultural areas during harvesting (Suski et al, ), no such high values were observed during this study. There was considerable variability in n INP during each flight, with the range in n INP values during any given flight greater than the range in average n INP across all flights, even in cases where CFDC measurements were only made over a narrow temperature range, illustrated in Figure .…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Across the entire ACAPEX study, number concentrations of INPs ( n INP ) ranged from near 0 up to a few ~10s L −1 at temperatures from −20 to −30 °C (Figure ), which are typical for ambient n INP values at these temperatures in relatively clean environments (DeMott et al, ). While concentrations as high as 100–1,000 L have been observed in heavily dust impacted environments (Boose et al, ; DeMott et al, ) and 100s L −1 in agricultural areas during harvesting (Suski et al, ), no such high values were observed during this study. There was considerable variability in n INP during each flight, with the range in n INP values during any given flight greater than the range in average n INP across all flights, even in cases where CFDC measurements were only made over a narrow temperature range, illustrated in Figure .…”
Section: Resultscontrasting
confidence: 58%
“…Filter measurements from the Central Valley on 12 February (not shown) were also very similar to those on 11 February in this region. This increase in n INP at these relatively warmer temperatures is commonly indicative of terrestrial biological INPs (Petters & Wright, ; Suski et al, ) and back trajectory analysis during this time period (Figure b) clearly showed air masses intercepting the terrestrial boundary layer prior to arrival at the Bodega Bay site (red lines). Previous studies have observed an increase in n INP following rain events associated with an increase in such terrestrial biological particle concentrations (Huffman et al, ; Prenni et al, ; Tobo et al, ), suggesting that intense rains have a feedback effect on the production and release of INPs (Morris et al ), as observed here.…”
Section: Resultsmentioning
confidence: 63%
“…, Suski et al. ). Once aerosolized, some microbes are well suited for survival in atmospheric environments.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes are aerosolized from all terrestrial and aquatic ecosystems (Wilson et al 2015, Joung et al 2017, including the surfaces of multicellular organisms, e.g., plants (Lindemann et al 1982, Burrows et al 2009a, Despr es et al 2012, and fluxes of bioaerosols are often generated or affected by anthropogenic activities (Taha et al 2006, Suski et al 2018. Once aerosolized, some microbes are well suited for survival in atmospheric environments.…”
Section: Introductionmentioning
confidence: 99%
“…Saarikoski et al 2014) and for INP measurements (e.g. McCluskey et al 2017McCluskey et al , 2018Suski et al 2018;DeMott et al 2017;Boose et al 2016a;Prenni et al 2013;. In particular, a 3-stage concentrator first described in Prenni et al (2013) and and based on the principal of virtual impaction, has been used in several field and lab studies in different environments, including agricultural fields, forest and marine environments.…”
Section: Introductionmentioning
confidence: 99%